1+(x-2/3)^3=37/64
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Giải:
\(1+\left(x-\frac{2}{3}\right)^2=\frac{37}{64}\Rightarrow\left(x-\frac{2}{3}\right)^2=-\frac{27}{64}\)
\(\Leftrightarrow x-\frac{2}{3}=-\sqrt{\frac{27}{64}}\Leftrightarrow x=-\sqrt{\frac{27}{64}}+\frac{2}{3}\)
Vậy \(x=\sqrt{\frac{27}{64}}-\frac{2}{3}\)
( 7.x - 15 ) : 3 = 2
7.x - 15 = 6
7.x = 6 + 15
7.x = 21
x = 3
không biết vì chưa học
88 - 3 ( 7 + x ) = 64
3 ( 7 + x ) = 88 - 64
3 ( 7 + x ) = 24
7 + x = 8
x = 1
(7.x -15):3=2
7.x-15=2.3
7.x-15=6
7.x=6+15
7.x=21
x=21:7
x=3
12.(x+37)=504
x+37=504:12
x+37=42
x=42-37
x=5
88-3(7+x)=64
3(7+x)=88-64
3(7+x)=24
7+x=24:3
7+x=8
x=8-7
x=1
dấu . là nhân nhé
1) 3x = 45 + 15 = 60
x = 60 : 3 = 20
2) 5x = 50 - 35 = 15
x = 15 : 5 = 3
3) (2x - 5) + 17 = 6
2x - 5 = 6 - 17
2x - 5 = -11
2x = -11 + 5
2x = -6
x = -6 : 2 = -3
4) 10 - 2(4 -3x) = -4
2(4 - 3x) = -4 - 10 = -14
4 - 3x = -14 : 2 = -7
3x = -7 - 4 = -18
x = -18 : 3 = -6
\(\left\{{}\begin{matrix}\left\{{}\begin{matrix}3x-15=45\Leftrightarrow3x=60\Leftrightarrow x=20\\35-5x=50\Leftrightarrow5x=-15\Leftrightarrow x=-3\end{matrix}\right.\\\left\{{}\begin{matrix}\left(2x-5\right)+17=6\Leftrightarrow2x+5=-11\Leftrightarrow2x=-16\Leftrightarrow x=-8\\10-2\left(4-3x\right)=-4\Leftrightarrow8-6x=14\Leftrightarrow6x=-6\Leftrightarrow x=-1\end{matrix}\right.\\\left\{{}\begin{matrix}-12+3\left(-x+7\right)=-18\Leftrightarrow-3x+21=-6\Leftrightarrow-3x=-27\Leftrightarrow x=9\\24:\left(3x-2\right)=-3\Leftrightarrow3x-2=-8\Leftrightarrow3x=-6\Leftrightarrow x=-2\end{matrix}\right.\\-45:5\left(-3-2x\right)=3\Leftrightarrow-15-10x=-15\Leftrightarrow10x=0\Leftrightarrow x=0\end{matrix}\right.\)
\(1+\left(x-\frac{2}{3}\right)^3=\frac{37}{64}\)
\(\left(x-\frac{2}{3}\right)^3=\frac{37}{64}-1\)
\(\left(x-\frac{2}{3}\right)^3=\frac{-27}{64}\)
\(\left(x-\frac{2}{3}\right)^3=\left(\frac{-3}{4}\right)^3\)
\(\Rightarrow x-\frac{2}{3}=\frac{-3}{4}\)
\(\Rightarrow x=\frac{-3}{4}+\frac{2}{3}\)
\(\Rightarrow x=\frac{-1}{12}\)
\(1+\left(x-\frac{2}{3}\right)^3=\frac{37}{64}\)
\(\Rightarrow\left(x-\frac{2}{3}\right)^3=\frac{37}{64}-1\)
\(\Rightarrow\left(x-\frac{2}{3}\right)^3=\frac{-27}{64}\)
\(\Rightarrow\left(x-\frac{2}{3}\right)^3=\left(\frac{-3}{4}\right)^3\)
\(\Rightarrow x-\frac{2}{3}=\frac{-3}{4}\)
\(\Rightarrow x=\frac{-3}{4}+\frac{2}{3}\)
\(\Rightarrow x=\frac{-9}{12}+\frac{8}{12}\)
\(\Rightarrow\frac{-1}{12}\)